2011
DOI: 10.1007/s11232-011-0120-0
|View full text |Cite
|
Sign up to set email alerts
|

Bose condensation: The viscosity critical dimension and developed turbulence

Abstract: We propose a model for studying the mutual influence of critical fluctuations in the vicinity of the critical point of phase transition to a superfluid state and the velocity fluctuations in the developed turbulence regime. We demonstrate the presence of two different regimes: the turbulence regime and the equilibrium regime. We show that the standard critical behavior can break in the turbulence regime. The viscosity becomes an infrared-irrelevant parameter in the equilibrium regime. We justify the assumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 8 publications
(39 reference statements)
0
11
0
Order By: Relevance
“…Such a modification of model E leads to some deviations from the standard field-theoretical approach, and we adopt it. We here continue the investigation begun in [4]. Our aim is to study different scaling regimes of the proposed model.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Such a modification of model E leads to some deviations from the standard field-theoretical approach, and we adopt it. We here continue the investigation begun in [4]. Our aim is to study different scaling regimes of the proposed model.…”
Section: Introductionmentioning
confidence: 89%
“…are not included in action (5), because it can be shown that they are IR-irrelevant. The renormalization of the proposed model was described in detail in [4]. In the renormalization group analysis, the following properties of the model must be applied:…”
Section: Field-theoretic Formulation Of the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…By inspection of the graphs we observe that all nontrivial diagrams in the term m ∂ t m vanish. In [20] it has been demonstrated that the linkage to critical statics is violated due to the inclusion of the velocity field, but the multiplicative renormalization can be recovered by considering a new charge associated with the interaction term m (ψ † ∇ 2 ψ − ψ∇ 2 ψ † ). More precisely, instead of writing this term with the charge g 3 (see Eq.…”
Section: A Canonical Dimensionsmentioning
confidence: 99%
“…In this work, we follow the third option (iii) by means of inclusion into the model description external velocity fluctuations. In this regard several generalization have already been proposed [13,20,21]. It has been shown that incompressible hydrodynamic fluctuations contribute sig-nificantly to the value of the ω w -index, which controls stability of large-scale regimes [9,17].…”
Section: Introductionmentioning
confidence: 99%